Association of multiple sclerosis with lateral olfactory tract usher substance (LOTUS), a possible endogenous inhibitor of axonal degeneration. (December 2015) - Takahashi, Keita; Takei, Kohtaro; Tanaka, Fumiaki
Abstract: Neuronal regeneration in the adult mammalian central nervous system (CNS) is restricted after brain injury, and some of myelin components and their common receptor, Nogo receptor‐1 (NgR1), have been identified as the key molecules for limiting axonal regeneration in the CNS. They have been widely studied as therapeutic targets to overcome the limitation of neuronal regeneration, and strategies using antagonism to NgR1 are expected for the development of the most promising therapies. Recently signaling through NgR1 was shown to be an underlying mechanism of axonal degeneration in multiple sclerosis (MS). Although MS is generally considered an autoimmune demyelinating disorder, axonal degeneration has recently attracted attention as an important pathological feature and one of the mechanisms leading to progressive neurological disability. These pathological and clinical features of MS suggest that molecules involved in limitation of axonal growth can be potential candidates for MS biomarker and therapeutic target, and recent studies have supported these hypotheses. We have previously identified a novel endogenous NgR1 antagonist and named it lateral olfactory tract usher substance (LOTUS). Our data showed that LOTUS promotes axonal growth through blocking of NgR1 signaling, suggesting that LOTUS could be an endogenous inhibitor of axonal degeneration. Furthermore, our recent study demonstrated an interesting variation of LOTUS level in the cerebrospinal fluid of MS patients that was well correlated with disease activity. Here, we review the association of MS with the molecules related to axonal growth including LOTUS, and discuss the clinical application of LOTUS as a promising biomarker and therapeutic target.